Relationship between Scientific Literacy and Critical Thinking of Prospective Teachers - Ivayuni Listiani; Herawati Susilo; Sueb Sueb (AL-ISHLAH: Jurnal Pendidikan, 2022)
The study aimed to analyze the relationship between scientific literacy and critical thinking in primary school teacher education undergraduate students. The subjects in the study were 127 students majoring in the Faculty of Teacher Training and Education at a private university in Madiun, Indonesia. The type of research used is correlational research with the research instrument multiple-choice tests. Data analysis was performed using the Pearson correlation test using SPSS version 25, which had previously been tested for normality and homogeneity. The normality test results of critical thinking ability and scientific literacy data obtained sig. 0.406, the data has been normally distributed. Furthermore, the data tested for homogeneity and scientific data literacy sig. 0.679 and critical thinking data sig. 0.944, so that the data was declared homogeneous and continued with the Pearson correlation test, which obtained a sig. 0.44. The results showed a relationship between scientific literacy and the critical thinking of prospective teacher students. This result indicated that understanding science requires good thinking, especially critical thinking.